Total Pressure Measurements in Vacuum Technology - Berman, A. (Elsevier Science, 2014)
Total Pressure Measurements in Vacuum Technology focuses on the measurement of low total pressure in hostile environments or in the presence of magnetic fields. This book emphasizes the general processes and problems involved in measurement techniques and physical principles on which vacuum gauges operate, rather than on the detailed description of the gauges. The design and techniques involved in the use of special instruments that determine "pressure or gas density, such as pressure converters or radioactive gauges, are also described. This publication is mainly intended for graduate students and research scientists who have a good general background in physics and engineering